Spawning Migration of the European Eel - Van den Thillart, Guido (Springer, 2017)
The European eel Anguilla anguilla is a common fish species in West European countries supporting several thousands of small-scale fisheries. In June 2007, it has been listed in Annex B of CITES after the 99% decline in recruitment observed over the last decades. A European Council Regulation was issued on September 2007 to arrest the collapse of the eel stock. In this book, we discuss the factors that may contribute to the collapse of the European eel population. With respect to conservation measures two important aspects have to be considered: quality and quantity of escaping silver eels. Clearly, a poor condition of the silver eels can never be compensated by large numbers. Qualitative parameters were thus far hardly available for management applications. The main goal of this book is to provide useful quality parameters for migrating silver eels, indicating their contribution to recruitment. The process of migration and maturation also provides information about the natural conditions for eel reproduction. Therefore, this book will also be very useful for eel aquaculture; it may provide tools for reproduction as well as for suppression of precocious maturation. An integrative approach regarding eel maturation requires a combination of ecology and physiology. In this book we included both aspects, and we hope that this will contribute to the restoration of the European eel population.